Pemanfaatan Media Sosial Bagi Pengembangan Pemasaran UMKM: Studi Kasus Hntnugraheniboutique Fashion - Bella Safitri; Azfa Mutiara Ahmad Pabulo (Lembaga Pengembangan Kinerja Dosen, 2024)
In the increasingly advanced digital era, social media has become a crucial tool in marketing strategies for Micro, Small, and Medium Enterprises (MSMEs). This article analyzes the use of social media in the marketing development of HNTnugraheniboutique Fashion, an MSME in the fashion industry based in Yogyakarta. The research methods employed include social media content analysis, online surveys targeting consumers, and in-depth interviews with the business owner. The findings reveal that HNTnugraheniboutique Fashion utilizes social media platforms, particularly Instagram and WhatsApp, to enhance visibility, build brand awareness, and boost sales. Despite these efforts, there remains potential to further optimize their social media usage for marketing purposes. Creative and relevant content proves effective in capturing consumer attention and influencing purchasing decisions. In conclusion, this research affirms that social media is an effective tool for MSMEs to develop marketing strategies. However, challenges such as competition and understanding digital consumer behavior underscore the need for further research to identify more specific and effective content strategies tailored for the MSME sector, particularly in Indonesia